2019
DOI: 10.1002/ijc.32806
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation sequencing reveals a novel role of lysine‐specific demethylase 1 in adhesion of rhabdomyosarcoma cells

Abstract: Lysine-specific demethylase 1 (LSD1), a histone lysine demethylase with the main specificity for H3K4me2, has been shown to be overexpressed in rhabdomyosarcoma (RMS) tumor samples. However, its role in RMS biology is not yet well understood. Here, we identified a new role of LSD1 in regulating adhesion of RMS cells. Genetic knockdown of LSD1 profoundly suppressed clonogenic growth in a panel of RMS cell lines, whereas LSD1 proved to be largely dispensable for regulating cell death and short-term survival. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…35 , 36 Collagen, one of the main components of the ECM is an important tissue barrier for cell migration, participates in cell survival and apoptosis, determines cell shape and controls cell differentiation and cell migration. 37 , 38 Collagen VI A1 (COL6A1) is widely present in all connecting tissues. Studies have shown that COL6A1 can trigger signaling pathways related to apoptosis, inflammation, and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…35 , 36 Collagen, one of the main components of the ECM is an important tissue barrier for cell migration, participates in cell survival and apoptosis, determines cell shape and controls cell differentiation and cell migration. 37 , 38 Collagen VI A1 (COL6A1) is widely present in all connecting tissues. Studies have shown that COL6A1 can trigger signaling pathways related to apoptosis, inflammation, and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that LSD1 instead plays an important role in anchorage independent growth and adhesion in RMS ( 71 ). Knockdown of LSD1 in RMS cells reduces expression of extracellular matrix genes and decreases clonogenic growth, reducing tumor growth, effects that are not assayed in short term growth screens.…”
Section: Lsd1 In Sarcomasmentioning
confidence: 99%
“…Evidence has shown that LSD1 mainly targeted histone methylation modification H3K4me2 and predominately induced transcriptional changes. 23 High levels of H3K4me2 at promoter regions may promote gene transcription, whereas low levels of H3K4me2 could inhibit transcription. [40][41][42] Therefore, we performed the ChIP assay for H3K4me2 to further explore the promoter modulation of SPRY4 upon LINC00675 overexpression.…”
Section: Linc00675 Binds To Lsd1 In the Nucleus Thus Enhancing The Bi...mentioning
confidence: 99%
“…20,21 LSD1 mediates gene activation and repression via removal of the methyl group (me) from mono-or dimethylated histone H3 at lysine 4 me 1/2 (H3K4me1/2) and lysine 9 (H3K9me1/2), which are endowed with the main specificity for H3K4me2. 22,23 Evidence has shown that LSD1 is upregulated and acts as an oncogene in various kinds of tumors. 24,25 Zhang et al 4 have revealed that LSD1 had upregulated expression in GC and positively contributed to GC development.…”
Section: Introductionmentioning
confidence: 99%